Trace elements content and antioxidant capacity in honey from protected phytogeographical regions in Uruguay - Arnaldo Moreni Real; Cristina Cabrera; Pablo Cracco; Mónica Cadenazzi; Florencia Pirotti; Estela Santos (Agrociencia Uruguay, 2023)
Honey is a natural sweet substance produced by honey bees, from the nectars of plant flowers and honey dew. The components of honey vary depending on the geographical site and the existing flora. The objective of this work was to characterize Uruguayan honeys produced in different regions by composition of trace elements (Cu, Fe, Mn, Mo, Zn, I, Se), the antioxidant capacity, the total polyphenols, and the palynological profile. Sixty-six honey samples were obtained in two seasons, spring-summer and summer-autumn, from three regions of protected areas, and a fourth region associated with human activities. The results obtained show that the contents of Cu and Mn were significantly higher (P<0.05) in region C (1.785 ug/g and 4.668 ug/g). For Mo, the Q region presented 1.060 ug/g, being significantly different (P<0.05) from the other regions. The total polyphenol content from region C was significantly higher (P<0.05) (66.442 mg GAE/100g). Likewise, the antioxidant capacity presented significant differences (P<0.05) for region C in the spring-summerseason. Some species, genus or botanical families were only found in a particular region. This work allows us to affirm that honey can be differentiated by its micronutrient content associated with the total polyphenol content, and a higher antioxidant activity for certain regions, given by the floral species present in the region and the type of soil.